Pegloticase and Methotrexate Cotherapy in Patients With Uncontrolled Gout With Prior Pegloticase Monotherapy Failure: Findings of an Open‐Label Trial - Orrin M. Troum; John K. Botson; Katie Obermeyer; Bo Chao; Yang Song; Jennifer Zarzoso; Kjerstina Gutierrez; Supra Verma; Lissa Padnick‐Silver; Brian LaMoreaux (ACR Open Rheumatology)
Objective Patients with uncontrolled gout have few treatment options. Pegloticase lowers serum urate (SU) levels, but antidrug antibodies limit SU‐lowering response and increase infusion reaction (IR) risk. Methotrexate (MTX) cotherapy increases pegloticase response rates and lowers IR risk in pegloticase‐naïve patients. Therefore, the question of re‐treating patients with previous pegloticase monotherapy failure has arisen. The ADVANCE open‐label trial examined pegloticase plus MTX cotherapy efficacy and safety following pegloticase monotherapy failure. Methods Patients with uncontrolled gout (SU levels ≥6 mg/dL, oral urate–lowering therapy failure or intolerance, and ≥1 gout sign or symptom) who previously lost SU‐lowering response to pegloticase monotherapy were included. Key exclusion criteria were moderate‐to‐severe IR or anaphylaxis to pegloticase, MTX contraindication, immunosuppressant administration, glucose‐6‐phosphate dehydrogenase deficiency, and estimated glomerular filtration rate <30 mL/min/1.73m2. After a 6‐week subcutaneous MTX run‐in (at 25 mg/wk), patients entered 24‐week pegloticase (at 8 mg biweekly) plus MTX treatment. The primary end point was SU‐lowering response rate during month 6 (SU levels <6 mg/dL for ≥80% of weeks 20–24). Safety was assessed via adverse events (AEs) and laboratory monitoring. Results Eleven patients began pegloticase plus MTX treatment (91% male patients, mean age 58.6 ± 11.3 years, mean ± SD SU levels 8.5 ± 3.2 mg/dL, 91% tophaceous). Previous pegloticase course was 2 to 27 infusions, with the last infusion admins being a mean ± SD of 3.7 ± 2.4 years before. One patient (9%) maintained response during month 6; 10 patients prematurely discontinued treatment (loss of SU lowering [n = 8], IR [n = 2]). Eight patients (73%) experienced ≥1 AE, most commonly gout flare. All AEs were mild or moderate. Conclusion Pegloticase plus MTX response rate following failed monotherapy was lower (9% vs 71%) and IR rate was higher (18% vs 4%) than in pegloticase‐naïve patients. These findings demonstrate the challenge of overcoming established antipegloticase antibodies and emphasize the importance of initiating immunomodulation before the first pegloticase exposure.